STUDY OF AGRICULTURAL MARKETING SYSTEM IN INDIA - Patil, Mr. Tushar (2010)
The conceptual theory of agriculture marketing encompasses the fields of operations, marketing and agricultural economics. It provides an array of options to explore the linkages between the producers, traders and buyers of the markets. As efficient, integrated, and responsive marketing systems form the core of economic development, it is of critical importance for optimal use of resources and to stimulate farmers to increase their output. The approaches used for studying the agricultural marketing include the commodity approach, the institutional approach, the functional approach, and the economic analysis of market performance. In this report, the emphasis is laid upon understanding the institutional structure of agricultural marketing in India, and using economic analysis to understand the problems associated with the fresh produce industry in the Indian context. The complexity of agricultural marketing system increases when a large number of small farmers, dispersed all over the country, use diverse production practices, and there are uncertainties over product characteristics and features between buyers and sellers. Issues such as these require an institutional approach to the marketing problem, which is offered by the transaction cost economics theory.